Simple productivity indices for lake ecosystems the case of Sampaloc lake. - Pempengco, Amalia Manrique ([College, Laguna] University of the Philippines at Los Baños, 1989)
Summary of an MSES thesis... presented in the RREM seminar series... February 16, 1989 at the IESAM seminar room, UPLB, College, Laguna.
Keywords: Lake ecology -- Philippines; Biotic communities -- Philippines; Aquaculture -- Philippines; Fisheries -- Philippines -- Mathematical models; Aquaculture -- Philippines -- Sampaloc Lake; Fisheries -- Philippines -- Mathematical models